ANALISIS MULTIKULTURALISME DALAM KONTEKS NASIONAL SERTA RELEVANSINYA TERHADAP ETNOPEDAGOGI PANCASILA DALAM SISTEM PENDIDIKAN DI INDONESIA - Suyani Armin; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze multiculturalism within the national context of Indonesia and examine its relevance to Pancasila ethnopedagogy in the education system. This research is motivated by the high level of cultural diversity in Indonesia, which has the potential to generate social conflict if not properly managed, as well as the strategic role of education in fostering values of tolerance, unity, and respect for diversity. The research employs a qualitative approach using a literature study (library research), by analyzing various scholarly sources, including national and international journal articles, books, and relevant previous studies. Data analysis was conducted thematically through data reduction, data display, and systematic conclusion drawing. The findings indicate that multiculturalism plays a significant role in developing awareness of diversity and inclusive attitudes, while Pancasila ethnopedagogy serves as an effective approach in internalizing local wisdom values such as mutual cooperation, tolerance, and social harmony in the learning process. The integration of these two concepts contributes to strengthening character education and reducing the potential for social conflict in multicultural societies. The novelty of this study lies in the synthesis of multiculturalism and Pancasila ethnopedagogy as a conceptual framework for developing an inclusive, contextual, and sustainable education system.